Implementasi Bauran Pemasaran Bisnis Retail Pada PT. Sentral Retailindo Dewata (PEPITO) - Ni Made Dwi Anjani; Majid Wajdi; Upayana Wiguna Eka Saputra (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Retail business is an activity related to selling goods and services directly to consumers. PT. Sentral Retailindo Dewata (Pepito), which is one of the retail businesses in Indonesia, experienced a decline in sales, low promotional contributions and different promotional media details in each period affecting finances and positioning of promotional items. Regarding this condition, PT. Sentral Retailindo Dewata (Pepito) must implement a marketing business strategy by implementing 7 marketing mix concepts consisting of product, price, promotion, place, people, process and physical evidence. This research examines the implementation of the retail business marketing mix at PT. Sentral Retailindo Dewata (Pepito) and the obstacles faced in implementing the marketing mix. This research uses a qualitative approach with data collection techniques of direct observation, interviews, document study and literature study. The data analysis method used in this research is qualitative descriptive analysis. The result of this research is the implementation of the marketing mix at PT. Sentral Retailindo Dewata (Pepito) is quite good, however, there are obstacles in the promotional and people marketing mix.